Deja Vu All Over Again? : The Mexican Crisis and the Stabilization of Uruguay in the 1970's - Blejer, Mario (IMF Working Papers; Working Paper ;, 1996)
Comparing the 1978-82 Uruguayan stabilization with the 1990-94 Mexican experience reveals that exchange rate based stabilization tends to increase the economy's vulnerability to unexpected shocks. An exchange rate rule, with full capital mobility, can only succeed if compatible financial policies are strictly adhered to--even when severe negative shocks take place--and if reliance on persistent capital inflows is not essential. This requires monetary restraint, even under serious recessionary conditions, and tight fiscal policies to moderate interest rates. The epilogues of both experiences demonstrate that abandoning the exchange rate rule in the wake of a shock, even if inevitable, makes future stabilization more difficult.